THE INFLUENCE OF EVENT EXPERIENCE ON EVENT SATISFACTION, POST-EVENT ATTITUDE & EMPLOYEE PRODUCTIVITY (STUDY ON PT XYZ CULTURE FEST EVENT) - Ahmad Jamil; Mahir Pradana; Rah Utami Nugrahani (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Corporate culture plays an important role in shaping employee engagement and productivity. PT XYZ held Culture Fest as a form of internalizing cultural values to all employees. This study aims to analyze the effect of experience during the event on satisfaction, post-event attitudes, and employee productivity. This research uses a quantitative approach with a survey method of 100 PT XYZ employees who participated in Culture Fest 2024. Data were collected through a Likert scale-based questionnaire, and the data were analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS software. The results showed that experience during the event had a significant effect on satisfaction and post-event attitudes. In addition, satisfaction with the event also had a positive effect on post-event attitudes, and these attitudes had a significant effect on employee productivity. This research confirms the importance of designing meaningful and relevant internal events as a strategic means to improve employee commitment and performance through strengthening organizational culture.